(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Emulsions are the most common form of skin care products. However, these systems may exhibit some instability. Therefore, when developing emulsions for topical application it is interesting to verify whether they have suitable physical and mechanical characteristics and further assess their stability. The aim of this work was to study the stability of emulsion systems, which varied in the proportion of the emulsifying agent cetearyl alcohol (and) sodium lauryl sulfate (and) sodium cetearyl sulfate (LSX), the nature of the oily phase (decyl oleate, cyclomethicone or dimethicone) and the presence or absence of pumice (5% w/w). While maintaining the samples at room temperature, rheology studies, texture analysis and microscopic observation of formulations with and without pumice were performed. Samples were also submitted to an accelerated stability study by centrifugation and to a thermal stress test. Through the testing, it was found that the amount of emulsifying agent affects the consistency and textural properties such as firmness and adhesiveness. So, formulations containing LSX (5% w/w) and decyl oleate or dimethicone as oily phase had a better consistency and remained stable with time, so exhibited the best features to be used for skin care products.